What Have We Learned about Lone Wolves from Anders Behring Breivik? - Raffaello Pantucci (Perspectives on Terrorism)
Anders Behring Breivik’s massacre on July 22, 2011 showed the danger that a well-organized Lone Wolf could cause. The methodical and calculated way with which he prepared and justified his act awoke security services the world over as to the potential menace that this form of terrorism can pose. As they revise their strategies, this article casts a preliminary eye on the case using a particular Lone Wolf prism of analysis to try to see what lessons can be learned from the case. Drawing on Breivik’s own writing and public sources, the article analyses his biography, the ideology he used to justify his act, the degree to which he seems to have been connected to others, his effectiveness, what role the Internet played and his mental competence all to try to draw some early lessons from the case. In concluding it offers some possible lessons learned that might offer practitioners some ideas of how to counter this sort of a threat in the future.